SPORT ORGANIZATIONS AND ENVIRONMENTAL PRESSURES: AN INSTITUTIONAL ANALYSIS - Mańkowski, Dobrosław Jerzy (Society Register, 2018)
Capitalism plays a significant role in the process of commercialization of sport. The bureaucratization, professionalization, politics and policy change legitimate organizational activities (Oliver 1992). The external process of bureaucratization, which is ‘the organizational manifestation of the rationalization of social life’ (Slack & Hinings 1994: 806) transforms sport organizations. The new environment of sport organizations moves them from voluntary organization to formal organizations with professional staff. This work identifies impact of external processes such as bureaucratization, professionalization and commercialization on sport organization. The focus is on the environmental pressures which change practices (procedures) in sport organizations. The article shows the changes in the field of sport and the processes of excluding voluntary, non-profit sport organization from competitions in elite sport. The last section of the article presents an alternative point of view on volunteers in sport industry.